2001
DOI: 10.1111/j.1095-8649.2001.tb00129.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid and fatty acid composition of female gilthead seabream during their reproductive cycle: effects of a diet lacking n‐3 HUFA

Abstract: In female sea bream Sparus aurata fed a control diet (C), ovarian levels of neutral lipids (NL) and polar lipids (PL) remained constant between November and March, while a decrease in NL content was observed in liver and muscle. In the same period, liver PL content increased, while no changes were observed in muscle. Between March and June ovarian NL and PL showed a strong decrease, while NL remained constant in liver and muscle. When fish were fed a diet lacking in n-3 highly unsaturated fatty acids, n-3 HUFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
19
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(29 citation statements)
references
References 50 publications
6
19
0
Order By: Relevance
“…Oocyte maturation involves transportation and accumulation of protein and lipid into oocytes (Tyler & sumpter 1996). Depending on species, lipids for oocyte accumulation could be obtained from muscle reserves or dietary intake (Almansa, Martin, Cejas, Badia, Jerez & Lorenzo 2001; Cejas, Almansa, Villamandos, Badia Balanos & Lorenzo 2003). The inferior ovarian mass in fish fed dietary protein 20% therefore could indicate that 20% dietary protein level could be below the optimal requirement for proper oocyte development in female swordtail.…”
Section: Resultsmentioning
confidence: 99%
“…Oocyte maturation involves transportation and accumulation of protein and lipid into oocytes (Tyler & sumpter 1996). Depending on species, lipids for oocyte accumulation could be obtained from muscle reserves or dietary intake (Almansa, Martin, Cejas, Badia, Jerez & Lorenzo 2001; Cejas, Almansa, Villamandos, Badia Balanos & Lorenzo 2003). The inferior ovarian mass in fish fed dietary protein 20% therefore could indicate that 20% dietary protein level could be below the optimal requirement for proper oocyte development in female swordtail.…”
Section: Resultsmentioning
confidence: 99%
“…Amongst the unsaturated fatty acids, oleic acid (OA, 18:1 n-9) was the most abundant followed by docosahexaenoic acid (DHA, 22:6 n-3) and eicopentaenoic (EPA, 20:5 n-3). The high levels of 18:1 n-9 and 22:6 n-3 in caviar reflect the importance of these fatty acids as energy reserve and a temporary reservoir of PUFA for future embryonic development, as clearly documented for other species [36,37].…”
Section: Proximate and Fatty Acid Composition Of Caviarmentioning
confidence: 90%
“…Few studies have addressed the issue of eggs quality and nutritional composition of diets; however, the duration of the period during which the broodstock should be fed a diet in order to affect the chemical composition of eggs is not completely clarified. Almansa et al [36] showed that 2 months of feeding before the spawning season were not sufficient to alter the chemical composition of egg quality in gilthead seabream (Sparus aurata). Leray et al [38] concluded that in rainbow trout (Oncorhynchus mykiss) only a long period of n-3 fatty acid deficiency is able to greatly alter egg lipids.…”
Section: Proximate and Fatty Acid Composition Of Caviarmentioning
confidence: 99%
“…We suggest that such evidence is due to a combined effect of fish adaptation to water temperature of Cage A fish and lipid mobilization for gonad development in fish caught in October. Fish from Cage B was indeed sampled at the beginning of its reproductive period (approximately from October to December in the Mediterranean area), when fish start to decrease food intake and use nutrients, especially lipids, from endogenous reserves for gonad growth . This is also in keeping with a reduction of K in October with respect to May.…”
Section: Discussionmentioning
confidence: 99%